“Lyrical Dialogue” by N. Gumilyov and A. Akhmatova: Communicative Aspect - N. V. Chaunina (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The attempts to analyze the “mutually addressed” lyrics of N. S. Gumilyov and A. A. Akhmatova within the framework of a communicative approach is analyzed in the article. The novelty of the study is in the fact that the particularities of the realization of dialogical intentions are determined, the principles of expressing addressing in lyric texts at the level of motive-shaped structure, visual-expressive and speech means are indicated. A comparative analysis of the artistic practice of the two greatest poets of the XX century is carried out. The material for analysis was the most representative lyric poems of A. Akhmatova and N. Gumilyov of 1900-1921, containing explicitly or implicitly expressed directives for dialogue, as well as devotional notes that indicate addressing each other. As a result of the study, it was revealed that in the poems of Akhmatova and Gumilyov there are similar communicative scenarios, the choice and content of which varies depending on the image of the addressee, the problematic thematic focus, as well as the specifics of the lyrical emotion. The “tools” of communicative interaction, due to the biographical context, the features of its personal interpretation, as well as the professional and philosophical development of colleagues in the “Workshop of poets”, are examined in detail.